1992
DOI: 10.1136/oem.49.7.489
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary impairment in workers exposed to silicon carbide.

Abstract: Two hundred and sixty seven workers employed in the manufacture of silicon carbide (SiC) were examined to determine the effects of exposure to contaminants (SiC, quartz, and SO2) in the workplace on pulmonary function. No exposure concentrations exceeded the current permissible limits. Ten

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…In the present study lung function, expressed by FEV 1 and FVC, was found to be lower in line operators and non-line operators than in non-exposed employees. This resembles the findings of some other studies in the smelting industry [Langard, 1980;Peters et al, 1984;Osterman et al, 1989;Marcer et al, 1992]. One study in an FeSi and FeCr producing smelter showed a reduced FVC in all exposed groups compared to an internal control group [Langard, 1980].…”
Section: Association Between Lung Function and Job Categoriessupporting
confidence: 87%
See 2 more Smart Citations
“…In the present study lung function, expressed by FEV 1 and FVC, was found to be lower in line operators and non-line operators than in non-exposed employees. This resembles the findings of some other studies in the smelting industry [Langard, 1980;Peters et al, 1984;Osterman et al, 1989;Marcer et al, 1992]. One study in an FeSi and FeCr producing smelter showed a reduced FVC in all exposed groups compared to an internal control group [Langard, 1980].…”
Section: Association Between Lung Function and Job Categoriessupporting
confidence: 87%
“…Occupational exposure in smelters producing FeSi, Si-metal, FeCr, and SiC alloys has been associated with impairment of lung function [Taddei et al, 1979;Langard, 1980;Peters et al, 1984;Osterman et al, 1989;Marcer et al, 1992]. Other studies have not confirmed these findings, however [Johansen and Vale, 1982;Cherniack and Boiano, 1983;Petran et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in two of the studies the association between exposure and impaired lung function was only significant in smokers 2 4. Moreover, an increased prevalence of respiratory symptoms among exposed SiC workers has been observed 1 5.…”
Section: Introductionmentioning
confidence: 86%
“…[1][2][3][4][5][6][7] In some of these studies, no association between pulmonary function and exposure has been found. 1,2 However, the cross-sectional design has several limitations.…”
mentioning
confidence: 99%